STUDI POLITIK PEMEKARAN : DINAMIKA AKTOR DALAM PEMBENTUKAN KECAMATAN SINGKEP SELATAN KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU TAHUN 2011-2012 - Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study entitled "Redistricting Political Studies: Actor Dynamics in District of South Singkep Establishment, Lingga regency, Riau Islands Province Year 2011-2012" The background of this research with the Government Regulation number 19 of 2008 concerning the District, where the formation on new districts in an area must meet the requirements that have been set. The formulation of the problem in this research is "How Actors Dynamics in District of South Singkep Establishment, Lingga Regency of Riau Islands Province in 2011-2012". Issues contained in this thesis is the existence of multiple interests of individuals and groups to perform South Singkep District Establishment and South Singkep District not deserved to become a new sub-district in Lingga Regency, Riau Islands Province. The method used in this study is a qualitative method that describes the data descriptively. Data collection techniques used were interviews and secondary data analysis. While the source of the data used are primary data obtained from the research site in the form of research informants and supported by secondary data.Based on the results of research conducted there are some of the findings related to actors dynamics of in the Establishment of the South Singkep District, Lingga Regency, Riau Islands province, namely Berhala Island rescue, preparation for the establishment of South Singkep District, political support, political lobbying, to the absence of the chairman of Lingga Regency parliament in Plenary Meeting of Lingga Regency Parliament , in the other words, the establishment of the South Singkep District, Lingga Regency, Riau Islands province is considered less effective.Keyword: Political Redistricting, Dynamics Actor, Actor Interest